Influence of Empowering Leadership to Employee Performance of Bank in Indonesia: Mediating Role of Trust in Manager - Juliansyah Noor; Datep Purwa Saputra (Faculty of Economics and Business Udayana University, 2022)
This article purposes to investigate the role of trust in manager in influences empowering leadership to employee performance. Drawing on a sample of 217 bank employees in Indonesia, path analysis was employed to analyze data. Firstly, the finds of a path analysis expressed that the influence of empowering leadership has a positive on trust in manager and employee performance. Furthermore, the study examined the mediating influence of trust in manager between empowering leadership and employee performance. The study shows that empowering leadership is not useable to culture of Western only, but it also suitable in Indonesian culture. The study's limitations are the data have been collected from banking employees. This can cause common method bias. In the banking case, empowering leadership can increase employee performance through trust in manager. Training should be prepared for banks leaders with a particular train on simplifying the behaviors of empowering in them. The study on investigating the influence of empowering leadership on employee performance via trust in manager as a mediator variable is very limited.